Factors influencing the adoption of mobile financial services in the unbanked population: The case of Chamwino District - Lema, Aulelius (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Master Degree in Science of Accounting and Finance of Mzumbe University